The influence of cattle breed on susceptibility to bovine tuberculosis in Ethiopia - Vordermeier, M.; Ameni, G.; Berg, S.; Bishop, Richard P.; Robertson, B.D.; Aseffa, A.; Hewinson, R.G.; Young, D.B. (Elsevier, 2012)
Bovine tuberculosis in domestic livestock such as cattle is an economically important disease with zoonotic potential, particularly in countries with emerging economies. We discuss the findings of recent epidemiological and immunological studies conducted in Ethiopia on host susceptibility differences between native zebu and the exotic Holstein–Friesian cattle that are increasingly part of the Ethiopian National herd, due to the drive to increase milk yields. These findings support the hypothesis that native Zebu cattle are more resistant to bovine tuberculosis. We also summarise the results of experimental infections that support the epidemiological data, and of laboratory experiments that suggest a role for the innate immune response, and in particular interleukin-6, in the outcome of bovine tuberculosis infection.